Now it’s your turn. Preschool children’s social and emotional interaction during tablet game sessions. - Yili Wang; Anu Kajamies; Tarja-Riitta Hurme; Jarmo Kinos; Tuire Palonen (Suomen Varhaiskasvatus ry. – Early Childhood Education Association Finland, 2022)
There is concern over social and emotional skill development in early childhood settings. The aim of this systematic observational study was to examine children’s prosocial and problem behaviors in small group settings. Especially, we studied how gender and closeness of friendships influence on children’s group level behavior. Altogether, nine video recordings were coded to observe peer interactions among children during tablet game sessions, where all 15 participants, aged 5 and 6 years, were allocated into four-member groups. The recordings were coded with a modified version of the Social Skills Improvement System Rating Scale. Social network analysis was employed to analyze the density and centrality of the interactions. Our results showed a wide variety of frequencies in different behaviors. In all, prosocial behavior was four times more typical than problem behavior, and there were more initiating than responding behaviors. Unlike prosocial behaviors, which were often verbal, most problem behaviors were nonverbal. The children interacted more actively with their best friends, and boys contributed more to both prosocial and problem behaviors than girls. A practical and concise peer interaction observation tool (PIOT) was developed for this study that can be used to follow children’s social and emotional skills in peer interactions.